Red Light Is Effective in Reducing Nitrate Concentration in Rocket by Increasing Nitrate Reductase Activity, and Contributes to Increased Total Glucosinolates Content - Signore, Angelo; Bell, Luke; Santamaria, Pietro; Wagstaff, Carol; Van Labeke, Marie-Christine (Frontiers in Plant Science, 2020)
Rocket cultivation is increasing to supply the expanding ready-to-eat market because of its unique taste, but crops are often over fertilized to avoid nitrogen deficiencies. This leads to nitrate accumulation in leaves, and the products of their degradation (nitrites and nitrosamines) have been related to several health problems. Nitrate concentrations in rocket and other leafy vegetables are subject to limits by the EU legislation, yet rocket holds a great nutritional value. Degradation products of glucosinolates (isothiocyanates) have been consistently linked with benefits to human health. We investigated the influence of nitrogen application (1 and 8 mM), species (Eruca sativa (L.) Cav. and Diplotaxis tenuifolia (L.) DC.) and light spectrum (full spectrum, red, blue and red+blue) on the nitrate concentration, nitrate reductase activity and glucosinolate content of rocket grown in a soil-less system. Red light decreased the nitrate concentration with respect to the blue spectrum (4,270 vs 7,100 mg·kg-1 of fresh weight, respectively), but such reduction was influenced by the species and the nitrogen level (significantly higher in D. tenuifolia and with the higher concentration of N). The nitrate reductase activity increased under red light in D. tenuifolia, with the lower N concentration. Rocket is known to contain several health-promoting compounds mainly antioxidants and glucosinolates, as secondary metabolites that act as part of plant defense mechanisms. The total content of glucosinolates was mainly affected by the species (D. tenuifolia showed the highest concentrations). Our results will help growers to tailor light spectra with the aim of reducing nitrate concentration and to remain within EU legislative limits, without any detrimental influence on other qualitative parameters in rocket.